ChemInform Abstract: Acentric and Chiral Heterometallic Inorganic‐Organic Hybrid Frameworks Mediated by Alkali or Alkaline Earth Ions: Synthesis and NLO Properties. Issue 40 (30th September 2014) - Tian, Chongbin; Zhang, Huabin; Du, Shaowu
Abstract Review: 94 refs.